Handbook of Purified Gases - Schoen, Helmut. (Springer Berlin Heidelberg : Imprint: Springer, 2015)
Technical gases are used in almost every field of industry, science and medicine and also as a means of control by government authorities and institutions and are regarded as indispensable means of assistance. In this complete handbook of purified gases the physical foundations of purified gases and mixtures as well as their manufacturing, purification, analysis, storage, handling and transport are presented in a comprehensive way. This important reference work is accompanied with a large number of Data Sheets dedicated to the most important purified gases. .